Implementasi Sistem Informasi Manajemen Pariwisata Dalam Promosi Destinasi Wisata Kabupaten Mamuju - Mauliah, ZalzaBilah Wulan; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The development of tourism in Mamuju Regency requires effective promotional strategies, especially in the digital era that demands speed and accuracy of information. The implementation of a Tourism Management Information System (TMIS) serves as a solution to improve the quality of information services, expand promotional reach, and strengthen the competitiveness of local tourist destinations. This article discusses the growing need for tourism digitalization in Mamuju, the benefits of implementing TMIS, and the challenges encountered during the implementation process. Using a literature review method and phenomenological analysis, this study finds that TMIS can have a significant impact on the dissemination of tourism information, increasing tourist visits, and managing tourism data in a more structured manner.